FACTORS CONTRIBUTING TO EFL LEARNERS’ SPEAKING PERFORMANCE - Areta, Dyah Pratiwi; Purwanti, Indah Tri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2021)
This research investigated the factors contributing to learners’ speaking performance and exploring the reasons why those factors are perceived by learners to contribute to their speaking performance. This was descriptive research that used both quantitative and qualitative approaches. The participants of this research were 28 EFL learners who were selected by using cluster random sampling. Closed-ended questionnaires, open ended questionnaires, and interviews were used to collect the data. The data from closed-ended questionnaires were analyzed quantitatively using the descriptive statistics of frequencies and percentages, while the data from open-ended questionnaires and interviews were analyzed qualitatively. Data from all sources were triangulated to validate the data. The result of the closed-ended questionnaire showed that the factors which contribute the most to learners’ speaking performance were the time for preparation and topical knowledge with the same percentages (97.4%). The least factor that contributes to learners’ speaking performance was the pressure to perform well (60.5%). Those factors contribute to learners' speaking performance in both positive and negative ways. These influences can either help motivate learners to speak English or even discourage them from doing so. It all depends on how learners’ value, respond to, and behave towards those factors. Furthermore, this research also gives contributions on factors that contribute to learners' speaking performance; those are vocabulary and interaction with native speakers.